Strength weakening and its micromechanism in water–rock interaction, a short review in laboratory tests - Zhang, Cun; Bai, Qingsheng; Han, Penghua; Wang, Lei; Wang, Xiaojie; Wang, Fangtian (International journal of coal science & technology, 2023)
Water–rock interaction (WRI) is a topic of interest in geology and geotechnical engineering. Many geological hazards and engineering safety problems are severe under the WRI. This study focuses on the water weakening of rock strength and its influencing factors (water content, immersion time, and wetting–drying cycles). The strength of the rock mass decreases to varying degrees with water content, immersion time, and wetting–drying cycles depending on the rock mass type and mineral composition. The corresponding acoustic emission count and intensity and infrared radiation intensity also weaken accordingly. WRI enhances the plasticity of rock mass and reduces its brittleness. Various microscopic methods for studying the pore characterization and weakening mechanism of the WRI were compared and analyzed. Various methods should be adopted to study the pore evolution of WRI comprehensively. Microscopic methods are used to study the weakening mechanism of WRI. In future work, the mechanical parameters of rocks weakened under long-term water immersion (over years) should be considered, and more attention should be paid to how the laboratory scale is applied to the engineering scale. Highlights This paper reviews the water weakening on rock strength and its influencing factors. Various microscopic methods for studying the pore characterization and weakening mechanism of WRI are compared and analyzed. We study the weakening mechanism of WRIs using microscopic methods. Future works on WRI laboratory tests were suggested.